The Relationship between Nutritional Status and The Incidence of Anemia in Students of LSPR Jakarta Institute of Co mmunication and Business - Friska Junita; Puri Kresna Wati; Rona Ulfah (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Female students who are classified as adolescents have a high risk of anemia, especially iron nutrition anemia. Female students generally have unhealthy eating habits. Students of LSPR Jakarta Institute of Communication and Business found many cases of suspected anemia. This is evidenced by the symptoms of female students coming to the clinic for health consultation. The design used in this study is quantitative with a Cross-Sectional approach method. The sample in this study is 75 female students from the LSPR Institute of Communication and Business in 2022 using sampling techniques using Random Sampling. The analysis used in this study was using the Chi-square test. The nutritional status of underweight female students was 45 (60%), while the incidence of anemia was 43 (57.3%), the chi-square test results obtained p-values of 0.000 < 0.05. There is a relationship between nutritional status and the incidence of anemia among LSPR communication and business institute students in 2022. Advice for LSPR. Health workers should be able to provide health promotion related to nutritional status and anemia in female students to change healthy living behaviors.